Analisis Kebutuhan Media Infografis Interaktif untuk Melatih Kemampuan Berpikir Change and Continuity dalam Pembelajaran Sejarah di SMA - Fauziyah Deldi; Hera Hastuti (YASIN, 2026)
The development of visual-based history learning media has received attention in various studies, but studies that specifically position the needs analysis of interactive infographic media to train Change and Continuity thinking ability remain limited. This study aims to analyze the need for developing interactive infographic media in history learning at senior high schools. This study used a descriptive qualitative approach with a needs analysis design at the initial stage of the ADDIE model. The research participants consisted of one history teacher, eight students as interview informants, and 36 students of class XI.F8 at SMA Negeri 1 Lareh Sago Halaban as essay test participants selected purposively. Data were collected through observation, interviews, essay tests, and documentation, then analyzed through data reduction, data display, conclusion drawing, and calculation of the percentage of students’ answers. The results showed that history learning was still dominated by the use of textbooks and teacher explanations, while students’ ability to understand change and continuity remained low. In the first question, 69% of students were unable to answer correctly, whereas in the second question, 83% of students were unable to answer correctly. These findings affirm that interactive infographic media is needed as a visual, concise, directed, and relevant alternative for history learning to train Change and Continuity thinking ability. The conclusion of this study indicates the importance of developing history learning media that can help students understand the relationship between change and continuity more systematically. The implications of this study provide an initial basis for developing interactive infographic media at the design and development stages of the ADDIE model, as well as input for history teachers in designing learning that is more visual, contextual, and oriented toward historical thinking skills.